Samer som övernaturliga väsen i fornnordisk litteratur - Kusmenko, Jurij (Scandinavistica Vilnensis, 2014)
The stereotypical features of the Sámi in Old Scandinavian literature have resulted from the interaction between the real features of the Sámi, features and motifs from Sámi folklore, and the stereotypical characteristics of Scandinavian supernatural beings expressing the idea of “otherness” (referring to giants and dwarves), the prevailing features of the giants being negative (the “hostile others”), the prevailing features of the dwarves being positive (the “friendly others”). However, the borrowing of features is not unidirectional: although the representation of the Sámi in the Scandinavian literature has been influenced by the representation of the giants and dwarves, also the Scandinavian giants and dwarves acquire certain features, originally characteristic of the Sámi.
Keywords: Representations of the Sámi; Old Scandinavian literature; “otherness”; giants and dwarves